Dimensionamento de rede de tubulações para transporte de biogás - Lopez, Thiago Fernando Magrini (2019)
There are many barriers that biogas chain must surpass to become a means of transforming an environmental passive into an economic asset. Technical solutions combined with the objective of reducing both acquisition and operating costs are responsible for breaking down many of these barriers. In regions with several biogas producers close to each other, a pipeline network enables the use of this gas in a single location, reducing costs compared to isolated installations and/or transport by trucks, whether for waste or for the gas itself. Therefore, engineering projects with this purpose should contemplate the dimensioning of the network of pipelines for the transportation of biogas, which has a reverse logic of operation to pipelines networks for transporting natural gas, due to the low pressures in which biogas is obtained. Given this, the present study carried out the dimensioning of the pipeline network of the COPEL R&D project in Entre Rios do Oeste, Brazil, using the premises that involve the biogas chain. The results show that it is possible to reduce piping diameter compared to current methodologies, reducing costs and increasing system reliability.